Pengaruh Komunikasi Interpersonal Dan Dukungan Sosial Terhadap Motivasi Mahasiswa Dalam Menyelesaikan Skripsi Di Tengah Pandemi Covid-19 Pada Mahasiswa Pendidikan Ekonomi Fakultas Ekonomi Universitas Negeri Padang - Nur Azizah Afwanda; Armida S (Jurnal Salingka Nagari, 2023)
This study intends to evaluate how the influence of interpersonal communication and social support on student motivatiaon in finishing the thesis during the Covid-19 Pandemic in Economics Education students, Faculty of Economics, Padang State University. This sort of research is descriptive associative research utilizing SPSS. The data collection strategy is via employing a questionnaire. Padang State University students who were enrolled in the Economics Education program at the Faculty of Economics were the participants in this study who were working on a skripsi for the 2015-2017 class, totaling 120 participants. With a total of 89 people responding to the survey, the method of sampling that was used was called accidental sampling. Data analysis with descriptive and inductive analysis The conclusions of this study are (1) Interpersonal communication and social support together have a favorable and substantial effect on student motivation in finishing a skripsi with results (sig 0.000 <0.05). (2) There is a favorable and significant influence of interpersonal contact on student motivation in completing the thesis with the outcome (sig 0.000 <0.05). (3) There is a favorable and significant effect of social support on student motivation in completing the thesis with the outcome (sig 0.041 <0.05).